Analisis Hukum Ekonomi Syariah Terhadap Penerapan Akad Murabahah pada Pembiayaan Pendidikan (Studi Kasus Unit Jasa Keuangan Syariah (UJKS) Annuqayah Guluk-Guluk Sumenep Jawa Timur) - Abdul Rahman (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2018)
AbstractIn either sharia banking or non-banking institutions, murabahah contract becomes an integral part of other products. Murabahah akad is a contract of sale and purchase of goods between a bank and a customer, which the bank notifies a cost of goods and increase the mutually agreed benefits. While the Educational Murabahah Akad in UJKS Annuqayah refers to the UJKS Annuqayah provides goods that support the learning process of education, such as needs of motorcycles, laptops, books and LCD projectors, and its payments was payed in installments and the UJKS Annuqayah do not add profit.In this study, the problems were as follows: first, what is the meaning of murabahah contract and the types of murabahah contract in the UJKS Annuqayah, second, how is the implementation of murabahah contract on education financing in the UJKS Annuqayah, third how is the review of Islamic economic law against murabahah agreement on education financing in the UJKS Annuqayah. While the purposes of were to understand and to describe akad murabaha on financing education in the UJKS Annuqayah, to understand the application of murabaha education, to understand and to describe the perspective of Islamic economic law towards the application of murabahah akad on education in the UJKS Annuqayah.The method used qualitative descriptive with field research approach, which is the study examined the theories that have been developed in the field of science related to the problems, looked for methods and research techniques both in collecting data and analyzing research that has been used by former researcher. The data was analyzed by using deductive theory. While the key informant was the director of UJKS Annuqayah, and the supporting informants were the head office of UJKS Annuqayah, the head office of women's payment point, the financing section, the payment section and the teller of UJKS Annuqayah.The results showed that the UJKS Annuqayah has 3 murabaha products; the murabahah business, the murabahah basic needs and the murabaha education. In murabahah education financing, the UJKS Annuqayah do not get a profit, but the UJKS gets cashback from deller divided between the UJKS Annuqayah and customer. According to the review of Islamic economic law, it is permissible because it is in accordance with Islamic legal principles based on the Imam Syafi'ie perspective and implemented with the principles of justice, no despotic action, mutual agreement and transparency on management. This is justified by Islam because it is spared of riba and gharar. Keywords       : murabahah akad, education financing, UJKS Annuqayah